(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Cholesteatoma is an abnormal accumulation of keratin-producing squamous epithelium in the middle ear, epitympanum, mastoid or petrous apex. It is a threedimensional epidermoid structure exhibiting independent growth, replacing middle ear mucosa, resorbing and replacing underlying bone. Although it is not a neoplastic lesion, it can be insidious and potentially dangerous to the patient. Objective: To find out the socio-demographic pattern, clinical presentation and complication of cholesteatoma. Materials and Methods: This prospective study of 50 cases was done in the Department of Otolaryngology and Head-Neck surgery, CMH, Dhaka adopting simple random sampling technique from July 2008 to Dec 2009. Data were collected by personal interview and clinical examination in a pre-designed data sheet and were analyzed by SPSS 20. Results: In this study, the highest number of patients (44%) was in the age group 11-20 years with a mean age of 17.2 years. Male were more affected (70%) and the male to female ratio was 2.33:1. Commonest symptom was otorrhoea (100%), followed by hearing impairment (80%), otalgia (16%), postauricular painful swelling (12%) and postauricular discharging sinus (10%). Extracranial complications were in 26% and intracranial complications in 12% of patients in this series. Abscess (temporal lobe + extra dural) were found in 02 cases (10%) by CT scan. A maximum number of patients had moderate conductive deafness (74.47%) followed by mild conductive deafness (19.15%) and only a few with severely mixed deafness (6.38%). Conclusion: Clinical presentation of cholesteatoma in this study was discharge and deafness. The discharge was thick purulent foul smelling, scanty, occasionally blood-stained. Grave intracranial complications in children developed because of illiteracy, poverty, lack of awareness and medical facilities mostly in the rural areas. So early diagnosis and prompt treatment was a necessity. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 66-70